2005
DOI: 10.3310/hta9200
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of routine databases in health technology assessment

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 199 publications
(76 reference statements)
0
55
0
7
Order By: Relevance
“…98,99 Both the Newton and Garner 98 and Raftery et al 99 papers were reviews of registers, clinical databases and routine databases with similar aims and objectives to those of our planned review. In effect, these reviews had already comprehensively addressed what we were setting out to do; therefore, to meet our objective of informing our own register design, this project became a 'review of reviews', although this was not the original intent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…98,99 Both the Newton and Garner 98 and Raftery et al 99 papers were reviews of registers, clinical databases and routine databases with similar aims and objectives to those of our planned review. In effect, these reviews had already comprehensively addressed what we were setting out to do; therefore, to meet our objective of informing our own register design, this project became a 'review of reviews', although this was not the original intent.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of detail in the review by Newton and Garner 98 meant that it was not possible to cross-reference the English registers identified in both reviews, but we assumed that a large number of the registers would have been identified by both reviews. Newton and Garner 98 did list six national treatment and device registers by name and these were all also included in the review by Raftery et al, 99 with Raftery et al 99 also presenting a more extensive list of named registers from across the UK. Around 60 of the registers identified by Raftery et al 99 had the potential for HTA and approximately half of these were group I registries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage from experimental research to health care (from bench to bedside, "vertical linkage") was only partially fulfilled. This corresponds with a limited use of socalled "disease-only registers" claimed by Raftery et al in a health technology assessment about routine databases [16]. Further criticism against the evidence of register research was formulated by Roovers concerning confounding, data quality, and business interests [17].…”
Section: Discussionmentioning
confidence: 99%
“…At registeret ikke er pasientidentifiserbart fratar oss muligheten for langtids overlevelsesstudier. En omfattende større analyse av medisinske kvalitetsregistre viser at få registre inkluderer kostnader ved behandling (15). Vårt register gir heller ikke mulighet for å beregne kostnader knyttet til de enkelte prosedyrer.…”
Section: Rapportering Og Publiseringunclassified